1996
DOI: 10.3109/02713689608997414
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface upregulation of intercellular adhesive molecule-1 (ICAM-1) by local interferon-gamma (IFN-γ) in the rat

Abstract: Inflammatory mediators such as interferon-gamma (IFN-gamma) are known to induce the expression of class II HLA (HLA-DR) and intercellular adhesion molecule 1 (ICAM-1) in a variety of cell types including epithelial cells. The coexpression of ICAM-1 and HLA-DR has been implicated in the pathogenesis of immune mediated ocular disease. We investigated the expression of ICAM-1 on the ocular surface of the rat eye following subconjunctival administration of IFN-gamma. A dose response study was performed using 100, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It appears that ICAM-1 is not critical to their migration from the vasculature into the stroma. Corneal epithelial cells and limbal vessel endothelial cells can express ICAM-1 14 -21 in response to inflammatory cytokines 35,36 such as tumor necrosis factor and interleukin-1␤ (both expressed in our model of epithelial abrasion). While ICAM-1 is known to contribute to lymphocyte adhesion and transendothelial migration, other adhesion molecules (eg, VCAM-1) also support lymphocyte transmigration.…”
Section: Icam-1 and Corneal ␥␦ T Cells 575mentioning
confidence: 99%
“…It appears that ICAM-1 is not critical to their migration from the vasculature into the stroma. Corneal epithelial cells and limbal vessel endothelial cells can express ICAM-1 14 -21 in response to inflammatory cytokines 35,36 such as tumor necrosis factor and interleukin-1␤ (both expressed in our model of epithelial abrasion). While ICAM-1 is known to contribute to lymphocyte adhesion and transendothelial migration, other adhesion molecules (eg, VCAM-1) also support lymphocyte transmigration.…”
Section: Icam-1 and Corneal ␥␦ T Cells 575mentioning
confidence: 99%
“…91,258,259 The integrated nature of OMIS and NALT systems may be important for ocular surface inflammation and inflammatory DED. 91,93,245,259262 Topically administrated solutions to the ocular surface are conducted by NLDs into the inferior meatus of the nose, where it reaches the NALT system.…”
Section: Discussionmentioning
confidence: 99%
“…For immunization purposes, we used a cocktail of four peptides rather than a single peptide. Previously it was shown that in mice, immunization with a mixture of 4 gD peptides induced better T-cell-mediated protective immunity than any individual peptide (5,6). This information could be advantageous for testing of vaccine efficacy with outbred populations, such as rabbits and humans.…”
Section: Resultsmentioning
confidence: 99%
“…The vascular nature of the OMIS (both circulatory and lymphatic systems) is involved in the process of aqueous outflow and lacrimal gland/duct drainage. The anatomical connection between the OMIS and NALT suggests an immunological connection and interdependency (6,10,35). The integrated nature of the OMIS and NALT systems may be important for ocular immunoprophylactic and immunotherapeutic vaccine development (5,10,(34)(35)(36)(37)39).…”
mentioning
confidence: 99%